Analysis of Investment Decisions at BMT Latansa Gontor Ponorogo - Kusumanisita, Apriliana Ika; Rusli, Lathiefa; Anugrah, Raditya Iqbal (Li Falah: Journal of Islamic Economics and Business, 2021)
This study aims to examine customer decisions in investing in BMT. The theory used to predict customer decisions in investing is the theory of reasoned action. The research method used is quantitative research with data analysis techniques Structural Equation Modeling (SEM). The results showed that the sharia system, product knowledge, religiosity, attitudes, risk perception, image, and investment intentions affected investment decisions.